Optimization of ammonia-nitrogen removal by an integrated system of lime precipitation and ammonia stripping for scheduled waste landfill leachate - Mat Lazim, Nurul Hanira (2018)
Various advanced waste disposal methods are available, nevertheless, landfilling is still widely adopted in most countries, due to its low cost and simplicity. However, the generation of a highly complex and polluted liquid leachate from landfill is a major concern as it threatens human health and environment. The presence of different constituents in leachate had made it difficult to be treated, and different treatment approach is needed dependent on the target pollutants. Despite the increasing number of documented scientific literatures in various wastewater and leachate treatment, the understanding of the leachate characteristics and treatment methods from scheduled waste landfill (SWL) are limited. Besides, SWL treatment need different approach as direct biological treatment is not suitable, due to its high NH3-N concentration that inhibits microorganism’s activity. These limitations have led to a thorough investigation in finding improved SWL leachate pre-treatment process on the removal of NH3-N by chemical and physical treatment prior to biological treatment. The main aim of the study is to find the right chemical and dosage for pH adjustment and apply ammonia stripping to reduce the concentration of NH3-N in SWL leachate. A preliminary study was carried out to find the most suitable chemicals, either hydrated lime, Ca(OH)2 or sodium hydroxide (NaOH); and the optimum dosage for effective NH3-N removal from SWL leachate and to raise pH prior to ammonia stripping. Batch jar test experiments with different types and dosage of chemicals ranging from 0 to 12 g L-1 were performed in this study. A Historical Data Design (HDD) of Response Surface Methodology (RSM) was employed to evaluate the parameters affecting the NH3-N, COD and colour removal efficiency. The result showed that Ca(OH)2 was found to be more effective in the removal of NH3-N (52%), COD (18%) and colour (65%) compared to NaOH, with less dosage required (5.9 g L-1). The lime pre-treatment only achieved half of removal efficiency, thus, further experiment using ammonia stripping technique to enhance NH3-N removal was adopted. A laboratory scale ammonia stripping column was constructed to evaluate the removal of NH3-N. Response surface methodology (RSM) was used to design the experiments incorporating four major factors at three levels; namely air/liquid ratio (20, 50 and 80), Ca(OH)2 dosages (4, 5 and 6 g L-1), packing height (20, 40 and 60 cm) and types of packing materials (Polyurethane foam, Polyurethane nylon and non-woven Polyester) where the interrelationship of the parameters on the removal of NH3-N were studied. The comparative analysis was done using RSM and artificial neural network (ANN) in a predictive model of the experimental data obtained in accordance with the central composite design. The ammonia stripping successfully removed NH3-N at 76% within 8 hours of treatment. Prolonged leachate treatment up to 12 hours successfully removed 88% of NH3-N. In addition, removal efficiencies of COD, Turbidity, Phosphate, Total Iron, Colour and Manganese were 5%, 55%, 49%, 100%, 38% and 18% after 12 hours of treatment, respectively. The validation results showed there was a good agreement between the predicted values obtained from the RSM and ANN model and the experimental NH3-N removal efficiency. The result also presented that RSM and ANN model gives comparable results, with R2 value of 0.9659 and 0.9347, respectively. This specifies that both models can be applied to describe the ammonia stripping process and can be used to predict the NH3-N removal from SWL leachate. The overall results in this study indicated that the integration of pre-treatment with Ca(OH)2 precipitation and ammonia stripping process is a feasible approach for NH3-N removal.